Analysis of paternal lineages legacy in Salta province, northwestern argentina. Issue 1 (December 2019) - Ferragut, J.F.; Albeza, M.V.; Acreche, N.; Castro, J.A.; Ramon, C.; Picornell, A.
Abstract: Seventeen Y-STRs included in the AmpFlSTR® Yfiler® PCR Amplification Kit were studied for 174 individuals from Salta province (northwest of Argentina). A total of 166 different haplotypes were identified. The Haplotype Diversity (HD) was 0.9992 and the Discrimination capacity (DC) was 95.4%. The high efficiency in forensic parameters demonstrates that this set of markers provides a powerful tool in forensic casework in Salta population. Haplogroup composition reflects the Amerindian and European legacy of this population together with a minor African contribution.